2021
DOI: 10.1002/stc.2749
|View full text |Cite
|
Sign up to set email alerts
|

Image‐based road crack risk‐informed assessment using a convolutional neural network and an unmanned aerial vehicle

Abstract: Rapid crack assessment is widely thought to be critical for monitoring and maintaining roads in appropriate conditions. In this paper, a novel crackaffected risk-informed assessment framework is proposed for the monitoring and maintenance of roads. The framework includes five steps: data collection, crack detection, crack location extraction, crack real-size calculation, and risklevel assessment. To support the framework, an unmanned aerial vehicle (UAV) is used to monitor roads and collect data. A state-of-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…to perform structural health monitoriing. 7 Ji et al 8 proposed a method of using the UAV to monitor road crack images, then use pixel statistics to detect cracks. In recent research, more scholars have paid attention to back-end image processing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…to perform structural health monitoriing. 7 Ji et al 8 proposed a method of using the UAV to monitor road crack images, then use pixel statistics to detect cracks. In recent research, more scholars have paid attention to back-end image processing.…”
Section: Introductionmentioning
confidence: 99%
“…According to the application type, there are two main directions of technical diagnostics: monitoring and diagnostics of rotating machinery, [1][2][3][4] and structural health monitoring (SHM), which is defined as a process of implementing a damage detection and characterisation strategy for various engineering structures. [5][6][7][8] According to the used technique, diagnostic methods can be divided into: destructive technique when maximum load or fatigue test of samples are performed 9,10 ; and non-destructive technique when the state of the structure is evaluated without causing damage to it. 11,12 Due to this advantage, the nondestructive technique has become the most common technique for technical diagnostics nowadays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] With the introduction of a convolutional neural network (CNN), researchers found that this type of network based on convolution, pooling, and fully connected layers allows for automated feature extraction, and many automated damage detection methods are based on this type of network. [22][23][24] Zhang and Yuen 25 proposed a novel crack detection system; it is a fusion features-based broad learning system that has the advantage of efficient training without GPU acceleration. Kim et al 26 proposed a shallow CNN-based architecture for surface concrete crack detection, and the hyperparameters of the proposed model were optimized to achieve the maximum accuracy of crack detection with the least calculation.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, researchers have proposed deep learning‐based methods 18–21 . With the introduction of a convolutional neural network (CNN), researchers found that this type of network based on convolution, pooling, and fully connected layers allows for automated feature extraction, and many automated damage detection methods are based on this type of network 22–24 . Zhang and Yuen 25 proposed a novel crack detection system; it is a fusion features‐based broad learning system that has the advantage of efficient training without GPU acceleration.…”
Section: Introductionmentioning
confidence: 99%